The principles of medical ethics and medical research - John Harris
In this paper I discuss the application of the principles of medical ethics and of medical research to the case of children and others whose consent to treatment and to research is problematic. Public health depends substantially on the possibility of ongoing research into all conditions which affect the health of the people. Constraints on this research are therefore a public health issue. Moreover and more importantly the possibility of predictive testing and indeed of screening for health-relevant conditions is an important public health tool, and limitations on the use of this tool are of great significance to public health medicine. Having considered the particular problems created by research and predictive testing on children for late-onset conditions I go on to discuss research on those whose consent is problematic more generally. I conclude with radical recommendations for the reform of The Declaration of Helsinki and of the International Ethics Guidelines for Biomedical Research Involving Human Subjects, prepared by the Council for International Organizations of Medical Sciences (CIOMS).